An introduction to nonparametric statistics - Kolassa, John Edward 1963- (Chapman & Hall/CRC texts in statistical science, 2021)
This book presents the theory and practice of non-parametric statistics, with an emphasis on motivating principals. The course is a combination of traditional rank based methods and more computationally-intensive topics like density estimation, kernel smoothers in regression, and robustness. The text is aimed at MS students"--